2019
DOI: 10.3390/horticulturae5010012
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Ascorbic Acid in Intact Acerola (Malpighia emarginata DC) Fruit by NIRS and Chemometric Analysis

Abstract: Acerola fruit is one of the richest natural sources of ascorbic acid ever known. As a consequence, acerola fruit and its products are demanded worldwide for the production of health supplements and the development of functional products. However, the analytical determination of ascorbic acid is time-consuming and costly. In this study, we show a non-destructive, reliable, and fast method to measure the ascorbic acid content in intact acerola, using near-infrared spectroscopy (NIRS) associated with multivariate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
(32 reference statements)
1
2
0
1
Order By: Relevance
“…The AA contents for chosen samples (AMP and ALIO) and acerola pulp in natura (AP) are presented in Table . The AA concentrations found in the present study are superior to those reported by Nóbrega, Oliveira, Genovese, and Correia (), between 406.0 and 765.3 mg AA/100 g DW for hot air dried acerola residue, and similar to the results presented by Moraes et al () that characterized fresh acerola fruit (1,190.65–2,187.06 mg AA/100 g FW). AP presented the highest concentrations ( p < .05) of AA (AP = 4,715.31 ± 107.98 mg AA/100 g DW), and even freeze drying process had a negative effect ( p < .05) on AA concentration (ALIO = 2,734.99 ± 59.28 mg AA/100 g DW).…”
Section: Resultssupporting
confidence: 79%
“…The AA contents for chosen samples (AMP and ALIO) and acerola pulp in natura (AP) are presented in Table . The AA concentrations found in the present study are superior to those reported by Nóbrega, Oliveira, Genovese, and Correia (), between 406.0 and 765.3 mg AA/100 g DW for hot air dried acerola residue, and similar to the results presented by Moraes et al () that characterized fresh acerola fruit (1,190.65–2,187.06 mg AA/100 g FW). AP presented the highest concentrations ( p < .05) of AA (AP = 4,715.31 ± 107.98 mg AA/100 g DW), and even freeze drying process had a negative effect ( p < .05) on AA concentration (ALIO = 2,734.99 ± 59.28 mg AA/100 g DW).…”
Section: Resultssupporting
confidence: 79%
“…Buritirana fractions were revealed to be a great source of vitamin C compared to several Brazilian tropical fruits [ 34 ]. Additionally, the vitamin C in the peel of buritirana represents about 12% of the vitamin C content of acerola ( Malpighia emarginata ), which after camu-camu ( Myrciaria dubia ), is considered one of the fruits with the highest concentration of vitamin C among Brazilian tropical fruits [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that machine vision technology [51] began to be used for the inspection of the external quality of fruits in 1998. In the stable stage, most studies applied e-nose [52], diffuse reflection [53], and near-infrared spectra [54] technologies. Machine vision technology [55] was further developed.…”
Section: Temporal Analysis Of Abstractmentioning
confidence: 99%